Pudarnya Kedudukan Dan Fungsi Pancasila Saat Ini (Studi Kasus: Kel. Bantan Timur Kec. Medan Tembung Kab. Deli Serdang) - Siregar, Aliqah Ayu Azzahra; Lubis, Muhammad Rezky Ananda; Zahra, Nayla; Sinaga, Syah Luna Elvanti; Ramadhani , Putri; Azzahra, Alya Irli; Siregar, Rita Febriani; Harahap, Wydia Rafika Sari (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
Pancasila is the ideological foundation of the Indonesian state and is expected to guide people’s behavior in social and population life. However, in recent years, there has been a noticeable decline in the understanding and practice of Pancasila values within society. This condition can be seen in the growing sense of individualism, the weakening of mutual cooperation, decreasing social concern, and reduced tolerance among community members. This study aims to examine the extent to which Pancasila values are understood and applied in population-related daily life in Medan Tembung District, as well as to identify the factors contributing to the fading of these values. This research employs a qualitative descriptive method with a field study approach. Data were collected through direct observation of the community environment, in-depth interviews with local residents from various age groups and occupational backgrounds, and supporting documentation. This approach was chosen to obtain a more realistic and comprehensive understanding of social conditions as they occur in everyday community life. The results of the study indicate that most residents are still familiar with Pancasila as the state ideology; however, their understanding tends to remain general and theoretical. In everyday practice, Pancasila values have not been consistently implemented. This is reflected in declining attitudes of mutual respect, low participation in community social activities, and a lack of concern for population-related issues within the neighborhood. Several factors contribute to this condition, including the influence of modernization, excessive use of technology, limited character education, and the decreasing role of families and community leaders in instilling Pancasila values. This study is expected to raise public awareness of the importance of reapplying Pancasila values in population life.